Profesionalizacija slovenskega literarnega proizvajalca - Dović, Marijan (Primerjalna književnost, 2006)
Professionalisation of the slovene literary producer: some introductory remarks. The paper treats the sociological problem of the professionalisation of the literary producer in Slovene literature, which has not often been discussed in literary studies. It systematically presents some introductory remarks concerning the degree of professionalism of literary writing in Slovene culture from the Enlightenment up to the present.
Keywords: sociologija literature; slovenski pisatelji; profesionalizacija; literarno ustvarjanje